A method and application of constructing honeycomb porous membrane based on two-dimensional nanosheets

By mixing superhydrophobic polymer with two-dimensional nanosheets and depositing it on the porous basement membrane, a honeycomb porous membrane was prepared, which solved the problem of insufficient solvent flux and dye retention rate of the existing two-dimensional membrane, and achieved efficient organic Waste liquid treatment and simple and easy-to-operate production process.

CN115532088BActive Publication Date: 2024-12-27HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211173661.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2024-12-27
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The existing two-dimensional membranes are insufficient in solvent flux and dye retention rate when treating organic waste liquids, and the production process is complex, which is not conducive to large-scale application.

Method used

The superhydrophobic polymer was mixed with two-dimensional nanosheets and deposited on the porous base membrane by vacuum suction filtration to prepare a honeycomb pore membrane, and its uniform honeycomb pore structure was used to improve solvent flux and dye retention.

Benefits of technology

It significantly improves solvent flux and dye removal rate, and the preparation method is simple and easy to operate, suitable for large-scale production and promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115532088B_ABST
    Figure CN115532088B_ABST
Patent Text Reader

Abstract

The present invention discloses a method and application of constructing a honeycomb porous membrane based on two-dimensional nanosheets, and relates to the technical field of membrane preparation. The method comprises the following steps: uniformly mixing a solution containing a super-hydrophobic polymer with a two-dimensional nanosheet dispersion and then depositing the mixed solution on a porous substrate membrane to obtain a honeycomb porous membrane. The solvent flux of the honeycomb porous membrane prepared by the present invention is much greater than the solvent flux of a membrane deposited with original two-dimensional materials, and the flux is increased by more than one order of magnitude. At the same time, the removal rate of the honeycomb porous membrane prepared by the present invention for small molecule dyes in the solvent can be as high as more than 99.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the technical field of membrane preparation, and in particular to a method for constructing a honeycomb porous membrane based on two-dimensional nanosheets and its application. Background technology:

[0002] With the rapid advancement of social industrialization, the resulting environmental pollution and energy shortage problems have become increasingly prominent, especially water pollution, which seriously threatens human water safety. The problem of industrial organic waste liquid is the main influencing factor of water pollution. At present, traditional methods of treating organic waste liquid generally face the problem of serious energy consumption. Therefore, how to treat organic waste liquid efficiently, greenly and sustainably is a direction that researchers must continue to study.

[0003] Membrane separation technology is widely used in many fields such as seawater desalination, sewage treatment and drug purification due to its advantages such as convenient operation, energy saving and high efficiency, high separation efficiency, recyclability, and ion and molecular level filtration. In recent years, with the birth of graphene, the emergence of new nanomaterials-two-dimensional materials has brought new ideas for the development of high-performance two-dimensional separation membranes with unique nanopores or nanochannels. The two-dimensional membranes prepared from two-dimensional materials such as graphene oxide, transition metal disulfides, covalent organic compounds, metal organic compounds have the advantages of regular interlayer spacing and interlayer channels, accurate size screening, and simple preparation process, which makes the development of two-dimensional membranes widely concerned. However, the existing two-dimensional membranes still have shortcomings, such as the low initial solvent flux of graphene oxide (GO) two-dimensional membranes and easy swelling in water, and the low initial flux of molybdenum disulfide two-dimensional membranes to organic solvents.

[0004] Nature Communications (Nature Communications, 2022, 13, 471) reported a method for synthesizing ultrafine metal oxide / reduced graphene oxide nanocomposite films by heterogeneous nucleation and growth control processes. The ultrafine nanoparticles in the membrane can inhibit the wrinkling of reduced graphene oxide nanosheets and improve the stability of the membrane. At the same time, as a pillar, the nanoparticles significantly increase the vertical interlayer spacing and lateral bending paths of the reduced graphene oxide membrane, thereby improving the solvent flux and dye interception capacity of the membrane. However, because more nanoparticle intercalation will cause interlayer blockage, resulting in limited flux improvement, the membrane production process is complicated, the membrane controllability is poor, and it is not conducive to mass production.

[0005] Patent CN 110124529A discloses a method for preparing a graphene oxide / MXene composite membrane, in which a graphene oxide solution and a MXene solution are mixed in different proportions, and the mixed solution is loaded onto the surface of a microfiltration membrane by vacuum filtration to obtain a composite membrane. Although this preparation method can increase the interlayer spacing of the membrane, reduce oxygen-containing functional groups, and thus reduce the resistance to water flow, thereby increasing the water flux, the flux of the composite membrane is extremely limited because the flux of the original GO membrane and the MXene membrane are both low, which is not conducive to large-scale application. Summary of the invention:

[0006] The technical problem to be solved by the present invention is to provide a method for constructing a honeycomb porous membrane based on two-dimensional nanosheets. The prepared honeycomb porous membrane has ultra-high solvent flux and excellent dye molecule retention rate, and can be efficiently used in the treatment of organic waste liquid.

[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0008] One of the purposes of the present invention is to provide a method for constructing a honeycomb porous membrane based on two-dimensional nanosheets, wherein a solution containing a superhydrophobic polymer and a two-dimensional nanosheet dispersion are evenly mixed and then deposited on a porous substrate membrane to obtain a honeycomb porous membrane.

[0009] Preferably, the super hydrophobic polymer is at least one of super hydrophobic polymers such as polydimethylsiloxane (PDMS), polydiethylsiloxane (PDES), and polyphenylmethylsiloxane.

[0010] The specific steps include:

[0011] Step 1: dissolving a super-hydrophobic polymer in an organic solvent to obtain a solution containing the super-hydrophobic polymer;

[0012] Step 2: uniformly mixing the solution containing the super-hydrophobic polymer obtained in step 1 with the two-dimensional nanosheet dispersion to obtain a mixed dispersion;

[0013] Step 3: depositing the mixed dispersion obtained in step 2 on the porous substrate membrane by vacuum filtration to obtain a composite membrane;

[0014] Step 4: Dry the composite membrane obtained in step 3 to obtain a honeycomb porous membrane.

[0015] In step 1, the organic solvent is at least one of isopropanol, ethanol, acetone, N,N-dimethylformamide and other organic solvents that can dissolve the super-hydrophobic polymer; the concentration of the solution containing the super-hydrophobic polymer is 0.1-0.5 mg·mL -1 ; The molecular weight of the super hydrophobic polymer is 3000-100000Da.

[0016] In step 2, the two-dimensional nanosheet dispersion is prepared by dispersing the two-dimensional nanosheets in deionized water at a concentration of 0.01-1 mg·mL -1 ; The two-dimensional nanosheets are at least one of two-dimensional nanosheets such as graphene oxide nanosheets (GO), molybdenum disulfide nanosheets, tantalum disulfide nanosheets, graphite phase carbon nitride (g-C3N4), transition metal carbon / nitride (MXene), and hexagonal boron nitride (h-BN); the mass ratio of the superhydrophobic polymer to the two-dimensional nanosheets is (0.5-200):1.

[0017] In step 3, the porous substrate membrane is one of porous membranes such as nylon membrane, polyethersulfone membrane, polyvinylidene fluoride membrane, polycarbonate membrane, anodized aluminum membrane, polyacrylonitrile membrane, etc., and the pore size of the porous substrate membrane is 100-450nm.

[0018] In step 4, the drying temperature is 50-80° C. and the time is 2-10 hours. By drying, excess solvent molecules are removed and a honeycomb pore structure is generated.

[0019] The second object of the present invention is to provide a honeycomb porous membrane prepared according to the above method. The thickness of the honeycomb porous membrane is 0.5-30 μm.

[0020] The third object of the present invention is to provide the application of the honeycomb porous membrane in the treatment of organic waste liquid.

[0021] Preferably, the organic waste liquid contains small molecule dyes.

[0022] Preferably, the small molecule dye is at least one of small molecule dyes such as Evans blue (EB), methyl blue (MB), calcein (CA), rhodamine B (RB), basic fuchsin (BF), methyl orange (MO), and neutral red (NR).

[0023] Preferably, the concentration of the small molecule dye in the organic wastewater is 10-50 μmol·L -1 .

[0024] Preferably, the organic waste liquid is treated by nanofiltration, and the pressure during nanofiltration is 0.01-10 MPa.

[0025] The principle of the present invention is: the interior of the honeycomb porous membrane prepared by the present invention has honeycomb pores of uniform size, and this structure provides more transmission paths for the solvent in the membrane, which is beneficial to the rapid transmission of solvent molecules. Therefore, the membrane has ultra-high solvent flux while maintaining excellent retention capacity.

[0026] The beneficial effects of the present invention are:

[0027] 1. The solvent flux (such as ethanol, isopropanol, methanol, water, etc.) of the honeycomb porous membrane prepared by the present invention is much greater than the solvent flux of the membrane stacked with the original two-dimensional material, and the flux is increased by more than one order of magnitude. However, the ultrafine metal oxide / reduced graphene oxide nanocomposite film synthesized by heterogeneous nucleation and growth control reported in Nature Communications (Nature Communications, 2022, 13, 471) can only increase the solvent flux by a single digit, and the synthesis process is complicated, which is not conducive to large-scale production.

[0028] 2. The honeycomb porous membrane prepared by the present invention can remove small molecule dyes in the solvent by more than 99.5%.

[0029] 3. The preparation method of the honeycomb porous membrane of the present invention is simple and easy to operate, and is easy to use on a large scale, which is conducive to promotion. Description of the drawings:

[0030] Figure 1 This is a scanning electron microscope image of a cross section of the MoS2 honeycomb porous membrane prepared in Example 1 of the present invention;

[0031] Figure 2 This is a scanning electron microscope image of the cross section of the GO honeycomb porous membrane prepared in Example 2 of the present invention;

[0032] Figure 3 This is a scanning electron microscope image of a cross section of a MoS2 layered film prepared in Comparative Example 1 of the present invention;

[0033] Figure 4 This is a scanning electron microscope image of the cross-section of the GO layered membrane prepared in Comparative Example 2 of the present invention. Specific implementation method:

[0034] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0035] Example 1

[0036] 1. Preparation of MoS2 honeycomb porous membrane:

[0037] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0038] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0039] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0040] 4. The membrane obtained in step 3 is dried at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane, the cross-sectional honeycomb pore structure of which is as follows: Figure 1 shown.

[0041] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0042] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1643 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.2%.

[0043] Example 2

[0044] 1. Preparation of GO honeycomb porous membrane:

[0045] 1. Dissolve 20 mg of PDMS (molecular weight 17000 Da) in 40 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0046] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 2 mL of 0.1 mg / mL -1 The GO nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0047] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0048] 4. The membrane obtained in step 3 was dried at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a GO honeycomb pore membrane. The cross-sectional honeycomb pore structure is as follows: Figure 2 shown.

[0049] 2. Application of GO honeycomb porous membrane in nanofiltration:

[0050] The GO honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 946 L·h -1 ·m -2 bar-1 , the retention rate of Evans blue is 99.5%.

[0051] Example 3

[0052] 1. Preparation of MoS2 honeycomb porous membrane:

[0053] 1. Dissolve 8 mg of PDMS (molecular weight 6000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0054] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0055] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0056] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0057] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0058] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 2800 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 98.9%.

[0059] Example 4

[0060] 1. Preparation of MoS2 honeycomb porous membrane:

[0061] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of acetone to obtain a concentration of 0.5 mg mL -1 PDMS / acetone solution.

[0062] 2. Mix the PDMS / acetone solution obtained in step 1 with 4 mL of 0.1 mg mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0063] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0064] 4. Dry the film obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore film.

[0065] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0066] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1554 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.6%.

[0067] Example 5

[0068] 1. Preparation of MoS2 honeycomb porous membrane:

[0069] 1. Dissolve 4 mg of PDMS (molecular weight 17000 Da) in 8 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0070] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0071] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0072] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0073] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0074] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 944 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue is 99.9%.

[0075] Example 6

[0076] 1. Preparation of MoS2 honeycomb porous membrane:

[0077] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0078] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0079] 3. The mixed dispersion obtained in step 2 is deposited on a polyvinylidene fluoride substrate with a pore size of 220 nm by vacuum assisted filtration.

[0080] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0081] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0082] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1720 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.2%.

[0083] Example 7

[0084] 1. Preparation of MoS2 honeycomb porous membrane:

[0085] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0086] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0087] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0088] 4. Dry the film obtained in step 3 at 80°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore film.

[0089] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0090] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1682 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.1%.

[0091] Example 8

[0092] 1. Preparation of MoS2 honeycomb porous membrane:

[0093] 1. Dissolve 8 mg of superhydrophobic polymer PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0094] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0095] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0096] 4. Dry the film obtained in step 3 at 60°C for 2 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore film.

[0097] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0098] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1620 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue is 99.5%.

[0099] Example 9

[0100] 1. Preparation of MoS2 honeycomb porous membrane:

[0101] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0102] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0103] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0104] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0105] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0106] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 40 μmol·L -1 The results showed that the ethanol flux was 1532 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.1%.

[0107] Example 10

[0108] 1. Preparation of MoS2 honeycomb porous membrane:

[0109] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0110] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 20 min to obtain a uniform mixed dispersion.

[0111] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum assisted filtration.

[0112] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0113] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0114] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1733 L·h -1 ·m -2 bar -1 The retention rate of methyl blue was 99.2%.

[0115] Embodiment 11

[0116] 1. Preparation of MoS2 honeycomb porous membrane:

[0117] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1 PDMS / isopropanol solution.

[0118] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0119] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0120] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0121] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0122] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 1673 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.0%.

[0123] Example 12

[0124] 1. Preparation of MoS2 honeycomb porous membrane:

[0125] 1. Dissolve 8 mg of PDMS (molecular weight 17000 Da) in 16 mL of isopropanol to obtain a concentration of 0.5 mg mL -1PDMS / isopropanol solution.

[0126] 2. Mix the PDMS / isopropanol solution obtained in step 1 with 4 mL of 0.1 mg / mL -1 The MoS2 nanosheet dispersion was mixed and then dispersed by ultrasound for 10 min to obtain a uniform mixed dispersion.

[0127] 3. The mixed dispersion obtained in step 2 is deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0128] 4. Dry the membrane obtained in step 3 at 60°C for 5 hours to remove excess solvent molecules and produce a honeycomb pore structure, thereby obtaining a MoS2 honeycomb pore membrane.

[0129] 2. Application of MoS2 honeycomb porous membrane in nanofiltration:

[0130] The MoS2 honeycomb porous membrane prepared in this example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the isopropanol flux was 892 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue was 99.6%.

[0131] Comparative Example 1

[0132] The difference between this comparative example and Example 1 is that PDMS is not added, and the other preparation steps are exactly the same.

[0133] 1. Preparation of MoS2 layered film:

[0134] 1. Add 4 mL of 0.1 mg mL -1 The MoS2 nanosheet dispersion was deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0135] 2. The film obtained in step 1 was dried at 60°C for 5 hours to remove excess solvent molecules, thereby obtaining a MoS2 layered film, the cross-sectional layered structure of which is as follows: Figure 3 shown.

[0136] 2. Application of MoS2 layered membrane in nanofiltration:

[0137] The MoS2 layered membrane prepared in this comparative example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 24.1 L·h -1 ·m -2 bar -1, the retention rate of Evans blue is 99.8%.

[0138] Comparative Example 2

[0139] The difference between this comparative example and Example 2 is that PDMS is not added, and the other preparation steps are exactly the same.

[0140] 1. Preparation of GO layered membrane:

[0141] 1. Add 2 mL of 0.1 mg mL -1 The GO nanosheet dispersion was deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0142] 2. The film obtained in step 3 was dried at 60°C for 5 hours to remove excess solvent molecules, thereby obtaining a GO layered film with a cross-sectional layered structure as shown in FIG. Figure 4 shown.

[0143] 2. Application of GO layered membrane in nanofiltration:

[0144] The GO layered membrane prepared in this comparative example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the ethanol flux was 18.9 L·h -1 ·m -2 bar -1 , the retention rate of Evans blue is 99.9%.

[0145] Comparative Example 3

[0146] The only difference between this comparative example and Example 12 is that PDMS is not added, and the other preparation steps are exactly the same.

[0147] 1. Preparation of MoS2 layered film:

[0148] 1. Add 4 mL of 0.1 mg mL -1 The MoS2 nanosheet dispersion was deposited on a nylon substrate with a pore size of 200 nm by vacuum filtration.

[0149] 2. Dry the film obtained in step 1 at 60°C for 5 hours to remove excess solvent molecules to obtain a MoS2 layered film.

[0150] 2. Application of MoS2 layered membrane in nanofiltration:

[0151] The MoS2 layered membrane prepared in this comparative example was fixed in a nanofiltration device, and the treatment concentration was 20 μmol·L -1 The results showed that the isopropanol flux was 10.5 L·h -1 ·m-2 bar -1 , the retention rate of Evans blue is 99.9%.

[0152] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for constructing a honeycomb porous membrane based on two-dimensional nanosheets, characterized in that: The solution containing the super-hydrophobic polymer and the two-dimensional nanosheet dispersion are uniformly mixed and then deposited on the porous substrate membrane to obtain a honeycomb porous membrane; The super hydrophobic polymer is at least one of polydimethylsiloxane, polydiethylsiloxane, and polyphenylmethylsiloxane; The two-dimensional nanosheet is at least one of graphene oxide nanosheet, molybdenum disulfide nanosheet, tantalum disulfide nanosheet, graphite phase carbon nitride, transition metal carbon / nitride, and hexagonal boron nitride.

2. The method according to claim 1, characterized in that The specific steps include: Step 1: dissolving a super-hydrophobic polymer in an organic solvent to obtain a solution containing the super-hydrophobic polymer; Step 2: uniformly mixing the solution containing the super-hydrophobic polymer obtained in step 1 with the two-dimensional nanosheet dispersion to obtain a mixed dispersion; Step 3: depositing the mixed dispersion obtained in step 2 on the porous substrate membrane by vacuum filtration to obtain a composite membrane; Step 4: Dry the composite membrane obtained in step 3 to obtain a honeycomb porous membrane.

3. The method according to claim 2, characterized in that: In step 1, the organic solvent is at least one of isopropanol, ethanol, acetone, and N,N-dimethylformamide; the concentration of the solution containing the super-hydrophobic polymer is 0.1-0.5 mg·mL -1 ; The molecular weight of the super hydrophobic polymer is 3000-100000Da.

4. The method according to claim 2, characterized in that: In step 2, the two-dimensional nanosheet dispersion is prepared by dispersing the two-dimensional nanosheets in deionized water at a concentration of 0.01-1 mg·mL -1 ; The mass ratio of the superhydrophobic polymer to the two-dimensional nanosheet is (0.5-200):

1.

5. The method according to claim 2, characterized in that: In step 3, the porous substrate membrane is one of a nylon membrane, a polyethersulfone membrane, a polyvinylidene fluoride membrane, a polycarbonate membrane, an anodized aluminum membrane, and a polyacrylonitrile membrane, and the pore size of the porous substrate membrane is 100-450 nm; In step 4, the drying temperature is 50-80° C. and the drying time is 2-10 hours.

6. The honeycomb porous membrane prepared according to the method according to any one of claims 1 to 5.

7. The honeycomb porous membrane according to claim 6, characterized in that: The thickness of the honeycomb porous membrane is 0.5-30 μm.

8. Use of the honeycomb porous membrane according to claim 7 in the treatment of organic waste liquid.

9. The use according to claim 8, characterized in that: The organic waste liquid contains small molecule dyes.

10. The use according to claim 9, characterized in that: The small molecule dye is at least one of Evans blue, methyl blue, calcein, rhodamine B, basic fuchsin, methyl orange and neutral red.

11. The use according to claim 9, characterized in that: The concentration of the small molecule dye in the organic waste liquid is 10-50 μmol·L -1 .

12. The use according to claim 9, characterized in that: The organic waste liquid is treated by nanofiltration, and the pressure during nanofiltration is 0.01-10MPa.